The role of nanoparticle inks in determining the performance of solution processed Cu2ZnSn(S, Se)4 thin film solar cells. (21st February 2016) - Qu, Yongtao; Zoppi, Guillaume; Beattie, Neil S.
Abstract: Cu2 ZnSnS4 (CZTS) nanoparticle inks synthesized by the injection of metal precursors into a hot surfactant offer an attractive route to the fabrication of Earth‐abundant Cu2 ZnSn(S, Se)4 (CZTSSe) thin film photovoltaic absorber layers. In this work it is shown that the chemical reaction conditions used to produce CZTS nanoparticle inks have a fundamental influence on the performance of thin film solar cells made by converting the nanoparticles to large CZTSSe grains in a selenium rich atmosphere and subsequent cell completion. The reaction time, temperature and cooling rate of the nanoparticle fabrication process are found to affect doping level, secondary phases and crystal structure respectively. Specifically, prolonging the reaction offers a new route to increase the concentration of acceptor levels in CZTSSe photovoltaic absorbers and results in higher device efficiency through an increase in the open circuit voltage and a reduction in parasitic resistance. Quenching the reaction by rapid cooling introduces a wurtzite crystal structure in the nanoparticles which significantly degrades the device performance, while elevating the reaction temperature of the nanoparticle synthesis introduces a secondary phase Cu2 SnS3 in the nanoparticles and results in the highest cell efficiency of 6.26%. This is correlated with increased doping in the CZTSSe absorber and the results demonstrate a route to controlling this parameter. © 2016 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons, Ltd. Abstract : The chemical reaction conditions used to fabricate Cu2 ZnSnS4 nanoparticle inks have a profound influence on the performance of completed Cu2 ZnSn(S, Se)4 thin film solar cells. Prolonging the reaction provides a means to increase the doping in the devices while the existence of wurtzite crystal structure significantly degrades the device performance. The highest efficiency is accompanied by secondary phase Cu2 SnS3 which results in the smallest voltage deficit relative to the energy band gap.